Briquettes as an Alternative Fuel to Wood for Circular Economy in Paddy Straw - Dogra, Ritu; Singh, Iqbal; Singh, Manpeet; Singh, Jasvarinder; Kumar, Dhiraj (International Journal of Bio-resource and Stress Management, 2024)
The study was conducted during rabi from November to March, 2019–20 at Department of Renewable Energy Engineering, PAU Ludhiana, Punjab, India to explore the new alternate biofuel for industry and cooking needs. Briquetting is one of the techniques that were not matured as required in the developing countries. Briquettes were prepared from chopped paddy straw, which is considered as waste and generally set on fire for clearing the fields. The aim of the investigation was to utilize field waste for thermal energy source in industry as well as for cooking in farming society. This endeavor could provide a ray of hope for paddy straw management in ex-situ application at large scale along with environmental benefits of preventing open burning. Briquettes were prepared on piston type briquetting machine with diameter 70 mm and the resultant fuel was compared with wood for physicochemical as well as thermal properties. It was observed from proximate and ultimate analysis that the paddy straw briquettes have similar properties as compared to the wood. Also, the calorific value of paddy straw briquettes was equivalent to wood and showed insignificant difference statistically. But the ash content of paddy straw briquettes was more than wood. The results showed that the calorific value, bulk density, ash content, and volatile matter of paddy straw briquettes were 15.29 MJ kg-1, 639.22 kg m-3, 23.46% and 64.03%, respectively. The paddy straw briquettes were evaluated in biomass cook stoves using water boiling test.